2004
DOI: 10.1002/art.11364
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II in the lesional skin of systemic sclerosis patients contributes to tissue fibrosis via angiotensin II type 1 receptors

Abstract: Objective. Tissue fibrosis in systemic sclerosis (SSc) is attributed to excessive deposition of extracellular matrix components produced by fibroblasts in skin lesions. Angiotensin II (Ang II), a vasoconstrictive peptide, is reported to have profibrotic activity as a result of induction of the extracellular matrix. The aim of the present study was to examine the expression of Ang II and its type 1 (AT 1 ) and type 2 (AT 2 ) receptors in affected skin and dermal fibroblasts from patients with SSc and to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 55 publications
2
89
2
2
Order By: Relevance
“…16 Recently, evidence has been presented that defined a role of Ang II in stimulation of collagen gene expression and protein turnover in cultured cardiac fibroblasts. 31,32 Here, our results demonstrated TGF-β activation induced by Ang II, which was in line with other studies that demonstrated Ang II regulated synthesis of TGF-β. 11,17 However, the effect of Ang II on MMPs and TIMPs in different studies remains controversial.…”
Section: Discussionsupporting
confidence: 92%
“…16 Recently, evidence has been presented that defined a role of Ang II in stimulation of collagen gene expression and protein turnover in cultured cardiac fibroblasts. 31,32 Here, our results demonstrated TGF-β activation induced by Ang II, which was in line with other studies that demonstrated Ang II regulated synthesis of TGF-β. 11,17 However, the effect of Ang II on MMPs and TIMPs in different studies remains controversial.…”
Section: Discussionsupporting
confidence: 92%
“…Such contaminants are difficult to trace because they are highly variable in terms of chemical structure and are active at low concentrations. Of note, levels of PDGF and angiotensin II have been found to be elevated in patients with SSc (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Ang II is implicated as a critical mediator of cutaneous wound healing and pathologic scarring (14). Ang II stimulates proliferation, migration and matrix production of human dermal fibroblasts (19)(20)(21)(22). Immunohistochemical staining of normal skin, wounded skin and hypertrophic scars has revealed that AT 1 and AT 2 expression are increased in scar epithelium and endothelium and that angiotensin-converting enzymes (ACE) activity is also increased, but reports of these findings do not describe immunostaining of the deep dermis (15,16).…”
Section: Introductionmentioning
confidence: 99%